ANALISIS PELAKSANAAN PROMOSI JABATAN PADA PT. TELKOM PEKENBARU - Fitri, Yulwinda; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research focuses on an implementation of job promotion done by PT.Telkom Pekanbaru which located in JendralSudriman Street No. 199.The descriptive quantitative method is used to analyze collected data. Thedescriptive quantitative method is an analysis by classifying data thus obtained, thenprocessed in accordance to its function. Processing results are then presented innumerical form that easier to understand. Statistical data processing is done to theextent of descriptive only and still has not reached the stage of generalization.The results of the analysis that has been done can be seen that theimplementation of the promotion is done by PT. Telekom Pekanbaru already included inthe category of “appropriate” to the terms set by the company. Implementation of jobpromotion at PT. Telkom based on the value of Competence (K) obtained by filling aquestionnaire that employees do online. The standard of competence at PT. Telkom isK3 and if someone wants to be promoted, the employee must obtain K2. K3 value set bythe company is 95 and the value of K2 range 95-115. The questionnaire contains anassessment of the employee who filled out by supervisors, fellow workers, subordinates,and the employees themselves. The questionnaire as a whole contains about discipline,knowledge of employees, the company common knowledge, knowledge about the job,and how the employee socialize with their work environment.Keywords: Human Resource Management, Job Analysis, and Job Promotion.